Perhitungan Harga Pokok Produksi dengan Metode Full Costing untuk Mengetahui Harga Pokok Produksi dan Meningkatkan Akurasi Perhitungan Laba/Rugi - Nuri Fitriani; Arry Irawan; Neneng Dahtiah; Riauli Susilawaty Hutapea; Sulistia Suwondo (Jurusan Akuntansi Politeknik Negeri Bandung, 2026)
The calculation of the cost of production (COGS) is important and needs to be considered by every business actor. The COGS calculation must be precise and accurate because COGS plays a role in determining the selling price and affects the company's profit/loss. Errors in determining the cost of production usually occur in business actors who only estimate the cost of their products or perform calculations but do not include all components of production costs. As happened in one of the micros, small and medium enterprises RD Sapala Shop which is engaged in manufacturing knitwear, which still relies on estimated costs in determining the cost of production, which causes selling prices to be less than optimal and profit/loss reports that are not accurate. The purpose of this study was to determine the calculation of the cost of goods manufactured according to the company and according to the full costing method and to improve the accuracy of the company's profit/loss calculation. This research method is descriptive quantitative. The COGS collection method used is the process cost method, while the COGS determination uses the full costing method approach to determine the cost of production which includes fixed and variable overhead costs.